1990
DOI: 10.1002/jsfa.2740510412
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate statistical methods applied to the differentiation of rum brands

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Herranz, et al [80] analysed the concentrations of selected free fatty acids (octanoic and decanoic acids) as well as other major congeners (ethyl hexanoate, ethyl octanoate, ethyl decanoate and ethyl dodecanoate) in 57 samples of bottled rum from Spain. Octanoic and decanoic acids were found in concentrations between 0.5-14 mg L −1 , while the high molecular weight esters were found at concentrations between 0.1-4.6 mg L −1 .…”
Section: Other Constituentsmentioning
confidence: 99%
“…Herranz, et al [80] analysed the concentrations of selected free fatty acids (octanoic and decanoic acids) as well as other major congeners (ethyl hexanoate, ethyl octanoate, ethyl decanoate and ethyl dodecanoate) in 57 samples of bottled rum from Spain. Octanoic and decanoic acids were found in concentrations between 0.5-14 mg L −1 , while the high molecular weight esters were found at concentrations between 0.1-4.6 mg L −1 .…”
Section: Other Constituentsmentioning
confidence: 99%
“…First studies on volatiles of rum were done by Maarse et al, who identified over 100 volatile compounds, and Nykänen et al, who analyzed in particular volatile fatty acids. In recent years, many groups identified rum volatiles, but the contribution of single volatile compounds to the overall aroma was not proven. De Souza et al compared the aroma of cachaça, a Brazilian spirit made from sugar cane, with the aroma of rum by means of gas chromatography–olfactometry (GC-O) and postulated several compounds to be the most potent odorants, for example, eugenol, ethyl phenylacetate, ethyl butanoate, and vanillin.…”
Section: Introductionmentioning
confidence: 99%
“…In particular techniques have had an impact on spectroscopy (Geladi, 2003). Using these resources, methods of development of food products and food analysis are generally simplified, such as control and monitoring processes (Catet et al, 1990;Robert, Bertrand, Devaux, & Grappin, 1987), food classification (Herranz, De La Serna, & Barro, 1990), detection of the adulteration of fruit pulp, honey and oils (Irudayaraj, Xu, & Tewari, 2003;Ozen, Weiss, & Mauer, 2003;Tay, Singh, Khrisnan, & Gore, 2002), sensory evaluation (Dever & Cliff, 1995;Gerbi, Zeppa, Antonelli, & Carnacini, 1997;Hough et al, 1996;Kjolstad, Isaksson, & Rosenfeld, 1990), determination of food fraud (Briandet, Kemsley, & Wilson, 1996) amongst other applications. Thus, chemometrics is effectively combined with multivariate analyses such as principal component analysis (PCA), discriminant analysis (DA) analysis and partial least squares (PLS), which provide the possibility of extracting resource spectra for investigating the spectral properties of samples (Lu, Yuan, Xu, & Qiang, 2000).…”
Section: Introductionmentioning
confidence: 99%